Second-look surgery plus hyperthermic intraperitoneal chemotherapy versus surveillance in patients at high risk of developing colorectal peritoneal metastases (PROPHYLOCHIP–PRODIGE 15): a randomised, phase 3 study. Issue 9 (September 2020) - Goéré, Diane; Glehen, Olivier; Quenet, François; Guilloit, Jean-Marc; Bereder, Jean-Marc; Lorimier, Gérard; Thibaudeau, Emilie; Ghouti, Laurent; Pinto, Amandine; Tuech, Jean-Jacques; Kianmanesh, Reza; Carretier, Michel; et al.
Summary: Background: Diagnosis and treatment of colorectal peritoneal metastases at an early stage, before the onset of signs, could improve patient survival. We aimed to compare the survival benefit of systematic second-look surgery plus hyperthermic intraperitoneal chemotherapy (HIPEC), with surveillance, in patients at high risk of developing colorectal peritoneal metastases. Methods: We did an open-label, randomised, phase 3 study in 23 hospitals in France. Eligible patients were aged 18–70 years and had a primary colorectal cancer with synchronous and localised colorectal peritoneal metastases removed during tumour resection, resected ovarian metastases, or a perforated tumour. Patients were randomly assigned (1:1) to surveillance or second-look surgery plus oxaliplatin-HIPEC (oxaliplatin 460 mg/m 2, or oxaliplatin 300 mg/m 2 plus irinotecan 200 mg/m 2, plus intravenous fluorouracil 400 mg/m 2 ), or mitomycin-HIPEC (mitomycin 35 mg/m 2 ) alone in case of neuropathy, after 6 months of adjuvant systemic chemotherapy with no signs of disease recurrence. Randomisation was done via a web-based system, with stratification by treatment centre, nodal status, and risk factors for colorectal peritoneal metastases. Second-look surgery consisted of a complete exploration of the abdominal cavity via xyphopubic incision, and resection of all peritoneal implants if resectable. Surveillance after resection of colorectal cancer was done according to the French Guidelines. The primary outcome was 3-year disease-free survival, defined as the time from randomisation to peritoneal or distant disease recurrence, or death from any cause, whichever occurred first, analysed by intention to treat. Surgical complications were assessed in the second-look surgery group only. This study was registered at ClinicalTrials.gov, NCT01226394 . Findings: Between June 11, 2010, and March 31, 2015, 150 patients were recruited and randomly assigned to a treatment group (75 per group). After a median follow-up of 50·8 months (IQR 47·0–54·8), 3-year disease-free survival was 53% (95% CI 41–64) in the surveillance group versus 44% (33–56) in the second-look surgery group (hazard ratio 0·97, 95% CI 0·61–1·56). No treatment-related deaths were reported. 29 (41%) of 71 patients in the second-look surgery group had grade 3–4 complications. The most common grade 3–4 complications were intra-abdominal adverse events (haemorrhage, digestive leakage) in 12 (23%) of 71 patients and haematological adverse events in 13 (18%) of 71 patients. Interpretation: Systematic second-look surgery plus oxaliplatin-HIPEC did not improve disease-free survival compared with standard surveillance. Currently, essential surveillance of patients at high risk of developing colorectal peritoneal metastases appears to be adequate and effective in terms of survival outcomes. Funding: French National Cancer Institute.